Vaccination Against SARS-Cov-2 among Patients with Parkinson’s Disease Based on the Results of COVPARK-LT Study - R. Kaladytė Lokominienė; G. Lokominaitė (Neurologijos seminarai)
Background. COVID-19 in patients with Parkinson’s disease leads to worsening of symptoms and development of severe/critical conditions; its long-term consequences are still being investigated. Data on vaccination against SARS-Cov-2 in Parkinson’s disease are inconsistent. There are no publications on this topic regarding Lithuania.